Preeclampsia and aspirin - Tae Gyu Ahn; Jong Yun Hwang (Obstetrics & Gynecology Science, 2023)
Preeclampsia (PE) is a multisystem disorder that is an important cause of maternal and perinatal deaths. Currently, delivery is the only final treatment for PE. This practice is usually accompanied by premature birth, which inevitably increases neonatal morbidities. Aspirin is a non-selective non-steroidal anti-inflammatory drug that irreversibly inhibits cyclooxygenase enzymes involved in converting arachidonic acid to prostaglandins and thromboxane. Aspirin inhibits thromboxane A2 production via platelet aggregation, thereby increasing the prostacyclin/thromboxane A2 ratio and reducing platelet aggregation. Since the first case report of aspirin’s potential use during pregnancy was reported in 1978, many studies have attempted to confirm the effect of aspirin on PE, and the results have been controversial. However, this preventive strategy is generally accepted in clinical practice. As evidence for aspirin’s prevention of PE has been accumulating, a recent study investigated the effectiveness of aspirin at high doses of 150 mg, which is higher than before. However, there is an ongoing debate about how much aspirin should be used during pregnancy and when to start aspirin therapy. Guidelines for the use of prophylactic aspirin during pregnancy vary slightly among countries and groups. In this article, we review and summarize the evidence regarding the use of aspirin for PE prevention.